A Qualitative Investigation of Academic Success: Insights from High School Achievers - Chophel, Yonten; Choden, Tshewang (Polaris Global Journal of Scholarly Research and Trends, 2024)
High School examinations present a significant hurdle for students, and achieving top performance requires a multifaceted approach. The proliferation of the internet has democratized access to knowledge, empowering individuals to pursue self-directed learning opportunities. This study sought to identify the common attributes of high-achieving students with the goal of inspiring and guiding underperforming students to emulate these successful behaviours and elevate their own academic performance. Employing a qualitative research methodology, the study utilized purposeful sampling to select seven (n=7) high performing students from Daga Central School. Thematic analysis revealed eleven shared attributes that contribute to academic success: a strong reading habit, focused engagement during classroom instruction, effective time management skills, meticulous organization of study materials, consistent review of learned materials, strategic use of information and communication technologies (ICT) to enhance learning, a supportive school environment, the presence of an inspiring role model, and a close-knit support system comprised of parents and teachers. These findings highlight that academic achievement transcends individual study habits; it is also highly influenced by external factors such as conducive learning environment, positive influence from educators, mentors, peers, and families. The study also discusses the implications of these findings for students, educators and other stakeholders in the educational landscape.